2018
DOI: 10.1152/ajpgi.00395.2017
|View full text |Cite
|
Sign up to set email alerts
|

Acute high-fat diet upregulates glutamatergic signaling in the dorsal motor nucleus of the vagus

Abstract: Obesity is associated with dysregulation of vagal neurocircuits controlling gastric functions, including food intake and energy balance. In the short term, however, caloric intake is regulated homeostatically although the precise mechanisms responsible are unknown. The present study examined the effects of acute high-fat diet (HFD) on glutamatergic neurotransmission within central vagal neurocircuits and its effects on gastric motility. Sprague-Dawley rats were fed a control or HFD diet (14% or 60% kcal from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(80 citation statements)
references
References 61 publications
6
73
1
Order By: Relevance
“…For example, microinjection of glutamate into the nucleus ambiguus (NA) partially inhibits gastric motility through the activation of the NMDAR-NO pathway, and microinjection of glutamate into the hippocampus inhibits gastric motility Evidence-Based Complementary and Alternative Medicine through NMDAR [35,36]. Moreover, one study showed that acute high-fat diet upregulated glutamatergic signalling in the DMV, thus increasing gastric motility [17]. ese studies indicated that the change of the glutamatergic system could affect gastric motility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, microinjection of glutamate into the nucleus ambiguus (NA) partially inhibits gastric motility through the activation of the NMDAR-NO pathway, and microinjection of glutamate into the hippocampus inhibits gastric motility Evidence-Based Complementary and Alternative Medicine through NMDAR [35,36]. Moreover, one study showed that acute high-fat diet upregulated glutamatergic signalling in the DMV, thus increasing gastric motility [17]. ese studies indicated that the change of the glutamatergic system could affect gastric motility.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated the existence of many gastric dilatation-sensitive neurons in the hippocampus [16], but the types of these neurons are unclear. In addition, glutamatergic signalling in the dorsal motor nucleus of the vagus (DMV) via the activation of N-methyl-daspartate receptors (NMDAR) increases gastric motility [17]; NMDAR is widely distributed in the hippocampus [18]. e stimulation of NMDARs results in calcium influx, the activation of neuronal nitric oxide synthase (nNOS), and an increase in the content of nitric oxide (NO) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies are needed to elucidate the distinct roles of GABA neurons in NTS and DMV in gastric motility. NTS‐GABA and NTS‐non‐GABA inhibitory neurons and NTS‐GLUT excitatory neurons exert an inhibitory and excitatory effect, respectively, on the DMV‐C‐e neurons …”
Section: Gastric Excitatory Vagal Motor Circuit (Gevmc)mentioning
confidence: 99%
“…NTS-GABA and NTS-non-GABA inhibitory neurons and NTS-GLUT excitatory neurons exert an inhibitory and excitatory effect, respectively, on the DMV-C-e neurons. 73 Moreover, within the NTS, the GABA, non-GABA, and GLUT neurons are interconnected. 74 NTS-CC-e neurons may also act to inhibit DMV-C-e neurons via the α2-receptors.…”
Section: G a S Tri C E Xcitatory Vag Al Motor Circu It (G E Vm C)mentioning
confidence: 99%
“…Memantine is believed to block the current flow through channels of NMDA glutamate receptor [33,34]. NMDA receptors are involved in the regulation of many gastric functions: 1) hydrochloric acid production [35], 2) glutamatergic, cholinergic and non-cholinergic pathways [36][37][38], 3) ghrellin mediated processes [12], 4) visceral pain [39], 5) chronic Helicobacter pylori infection [40], 6) gastric accommodation and emptying [41] and other. NMDA receptors also participate in the brain-gut axis regulation [42] and function of the lower oesophageal sphincter [43].…”
Section: Discussionmentioning
confidence: 99%